Clinical analysis of 82 cases of acute promyelocytic leukemia with PML-RARα short isoform in children and adults - Huang, Qiaolin; Zhang, Yicheng; Zheng, Miao (Frontiers in Oncology, 2024)
Background: Acute promyelocytic leukemia (APL) with PML/RAR α fusion gene is a distinct variant of acute myeloid leukemia. According to the different break sites of the PML gene, there are three transcripts: Long (bcr1), Variant (bcr2) and Short (bcr3). Methods: We retrospectively analyzed 82 APL cases with PML-RARα short isoform. Results: A total of 384 patients with APL were seen, of which 85(22.14%) had PML/RAR α short isoform (bcr3) and 82 met the inclusion criteria. The median age was 33.5 years (range, 2-72 years). The incidences of hemorrhage in the intermediate-and high-risk group were higher, but only the incidence between medium and low risk differed statistically (P=0.006), and the incidences of fever, fatigue, splenomegaly, and lymph node enlargement and differentiation syndrome (DS) in those groups were not statistically significant (P>0.05). FLT3 gene mutation rate and the mortality rate of the high-risk group were significantly higher than that of other groups (P=0.040 and P=0.004, P=0.041 and P=0.037, respectively). The mortality rate was lowest (4.44%) in the group treated with ATRA combined with arsenic and anthracycline. The 3-year OS and the 3-year DFS of the low and intermediate-risk group were better (P=0.019 and P=0.017, respectively). Conclusions: ATRA combined with arsenic and anthracycline had significant impact on outcomes in APL with PML-RARα short isoform.